Accounting rules and the signaling properties of 20 percent stock dividends. - Rankine, Graeme W.; Stice, Earl K. (The Accounting Review, 1997)
Stock dividends which increase outstanding shares by less than 25 percent require a transfer from retained earnings of the market value of the new shares, a much larger transfer than that required for stock dividends of 25 percent or more. Choosing a distribution factor near, but below, 25 percent may be an indication of management optimism that future income will replenish retained earnings, avoiding constraints on future cash distributions. In this study, firms declaring 20 percent and 25 percent stock dividends are compared. The 20 percent stock dividend firms exhibit significantly greater announcement-period abnormal returns and significantly greater post-declaration cash dividend growth. These effects are greatest for firms incorporated in states where the level of retained earnings more strictly constrains the payment of cash dividends.